Web-based educational portal on EMF for children - Ng, K.H.; Tan, L.K.; Kadri, Nahrizul Adib; Lee, S.E.; Siow, H.L. (2006)
The last decade has seen an unprecedented rise in the usage of mobile phone technology. This sudden technological shift has confused and concerned the general public over potential health risks due to electromagnetic field (EMF) radiation. This uncertainty is largely due to unfamiliarity with the technological concepts involved, and is best addressed via education. In this paper, we will introduce the efforts of the World Health Organization (WHO) and the University of Malaya, Malaysia, to design and implement a web-based educational portal on EMF for children. This portal uses Macromedia® Flash®, and utilizes multimedia and interactive exhibits as well as simple instructional language and concepts to introduce the curriculum. ©2006 IEEE.